Sukuk Characteristics and Financial Performance Among Top 100 Listed Companies in Malaysia - Noor Arzmyra Hazrin; Aliana Shazma Amir; Siti Nor Junita Mohd Radzi (Universitas Medan Area, 2022)
This study examines the relationship between sukuk characteristics and financial performance by top 100 Malaysian public listed companies. The study uses 100 firm-year observations drawn from the population of non-financial companies in 2021. To achieve the objectives of this study, quantitative method of analysis is employed. Agency theory supports the application of several governance strategies to control